Long-term changes in circulation conditions over southern Poland for the period 1874–2020 - Bielec-Bąkowska Zuzanna (Miscellanea Geographica: Regional Studies on Development, 2022)
The study presents the long-term and annual trends in atmospheric circulation over southern Poland for the period 1874–2020. The analysis takes into account both the type of atmospheric circulation, and the types of air mass and atmospheric fronts. The study showed that there has been a noticeable decrease in the frequency of anticyclonic types of circulation and of air advection from the west and east, and a slight increase in advection from the south, as well as the presence of anticyclonic centres and cyclonic troughs. The research also found considerable changes in the frequency of the presence of polar air and of stationary and occluded fronts, as well as of days with several fronts moving over the study area.